Disfluent Responses to Job Interview Questions and What They Entail. Issue 5 (3rd July 2016) - Brosy, Julie; Bangerter, Adrian; Mayor, Eric
Abstract : Conversation is governed by expectations of timely responding. Violations of these expectations are grounds for inference by other participants. These inferences may be at odds with identities respondents try to project. In job interviews, candidates' responses are used to make hiring decisions. Candidates trade off between (1) delaying response initiation to search for an appropriate response at the risk of appearing inept and (2) responding quicker but less appropriately. In a corpus of job interviews, response delays predicted the probability of inappropriate initial responses and decreased hireability ratings, illustrating how unintended aspects of conversational delivery can entail social and institutional consequences beyond the conversation itself.